CAFE: Collaboration Aimed at Finding Experts. (19th July 2010) - Rubens, Neil; Vilenius, Mikko; Okamoto, Toshio; Kaplan, Dain
Research-oriented tasks continue to become more complex, requiring more collaboration between experts. Historically, research has focused on either finding a single expert for a specific task Expertise Finding (EF), or trying to form a group that satisfies various conditions Group Formation (GF). EF is typically group context agnostic, while GF requires complex models that are difficult to automate. This paper focuses on the union of these two, forming groups of experts. We concentrate in this paper on the expertise aspect of GF, since without the needed expertise, regardless of other factors, the task cannot be accomplished.